ANALISIS KESALAHAN BERBAHASA PADA ARTIKEL PENDIDIKAN KORAN RADAR BANTEN DAN IMPLIKASINYA DALAM PEMBELAJARAN BAHASA INDONESIA DI SD DILARAF ISLAMIC SCHOOL - Nurul Oktafiani; Goziyah Goziyah; Ilmi Solihat (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2022)
AbstractThe purpose of this research is to characterize the following types of errors made by authors of educational articles published in the Radar Banten newspaper: 1) improper use of capital letters; 2) improper use of italics; 3) improper use of prepositions; 4) improper use of affixes. This study uses a sample of three scholarly articles to hone in on a certain topic. Reading and making notes were used to compile the data. In contrast, human beings, not mechanical ones, are used in the data collection process. Method for analyzing information gathered by a qualitatively descriptive approach to data collection. Based on the findings of this investigation, the educational articles published in the Radar Banten newspaper contain a total of 22 instances of incorrect Indonesian spelling. These 22 instances are broken down as follows: 1) 5 instances of incorrect capitalization, 2) 15 instances of incorrect italicization, 3) 1 instance of incorrect prepositional phrase formation, and 4) 1 instance of incorrect affixes. The findings of this research can be incorporated into lessons for Dilaraf Islamic School's Indonesian language program. Keywords: analysis of language errors, articles, learning.